2022
DOI: 10.1055/s-0042-1744286
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Preeclampsia: Suggested Guidance on the Use of Biomarkers

Abstract: Objective It is a challenge to consider preeclampsia (PE) diagnosis and management in low and middle-income settings, where it represents a major public health concern. The placenta is the underlying cause of disease, and the plasma concentrations of proangiogenic and antiangiogenic factors released by the placenta can reflect the risks of disease progression. Antiangiogenic proteins, such as soluble fms-like tyrosine kinase 1 (sFlt-1), and proangiogenic, like placental growth factors (PlGF), are directly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Our data, when comparing outcomes among cases with altered sFlt-1/PlGF ratio (using 38 as the threshold) did not present significant differences. Nevertheless, we had limited number of cases and only very few with sFlt-1/PlGF ratio over 85 (the most used ratio for PE diagnosis) 27 . Regardless, biological samples were collected at the time of SARS-CoV-2 infection and not at the time of PE diagnosis, which may have experimental implications.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, when comparing outcomes among cases with altered sFlt-1/PlGF ratio (using 38 as the threshold) did not present significant differences. Nevertheless, we had limited number of cases and only very few with sFlt-1/PlGF ratio over 85 (the most used ratio for PE diagnosis) 27 . Regardless, biological samples were collected at the time of SARS-CoV-2 infection and not at the time of PE diagnosis, which may have experimental implications.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of a late abortion in asymptomatic pregnant women is independently correlated with sFlt-1 and PlGF ( Figure 2 C,F) [ 47 ]. Despite this, Costa et al concluded that the sFlt1/PlGF ratio should only be used to exclude pre-eclampsia at 20–36 weeks of gestation and cannot replace the standard approaches to the diagnosis of the disease [ 48 ].…”
Section: Short-term Pre-eclampsia Predictions Using the Sflt1/plgf Ratiomentioning
confidence: 99%
“…Recently, another biomarkers, like the soluble fms-like tyrosine kinase 1 (sFlt-1), endoglin, PlGF, neurokinin-B have been used to try to predict the preeclampsia's onset and/or preeclampsia's complications ( 15 20 ). The measurement of sFlt-1/PlGF ratio or PlGF alone is endorsed by some guidelines to rule out PE, since the negative predictive value of these tests are very high and reliable ( 14 , 21 ). Neurokinin-B, a neuropeptide produced by the placenta, also can be a possible role in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%